Brands and other mythological animals - Kaltzada González, Pilar (Revista Española de Comunicación en Salud, 2025)
For some people, Primary Healthcare is the access door to complex services that will come later. For others, it is the foundation of the health system on which citizen rights and guarantees of well-being are built. Primary Care suffers from a chronic bad image. However, numerous studies indicate that the reality does not correspond to the image of a "state of demolition" that it seems to have today. The image of a service, and Primary Healthcare is it, is built on perceptions. In many cases, immune to the weight of the data. If the image is an amalgam of perceptions, the brand is a conscious construction that combines vision, strategy and resources that are used to transfer the value of what is offered in a structured and conscious way. A brand is the distinctive set of ideas and feelings that people have towards a service, product or organization to which it refers. It is a relationship that generates feelings, thoughts, and actions connected to the promise of value. Primary Healthcare is a service whose potential and image are far below the real value of its brand. Primary Healthcare is based on a crisis narrative and a perception of deterioration that makes it difficult to manage its brand. A brand that must be redefined from the prism of the value it brings, a unique value: the health as the first social right.